Institutional transformation of the financial basis of the local self-government - Sergey S. Shestopal, Serhii V. Boldyriev, Tatyana V. Steshenk , Oleksandr O. Frolov, Anton S. Chyrkin, (Opción, 2019)
The study investigates the institutional transformation of financial basis of the local self-government in the Czech Republic, Hungary and Poland via comparative qualitative research methods. As a result, the Czech Republic also failed to avoid a downturn, but since 2010, the economy has started to grow and, consequently, there has been an increase in GDP at 1%. In conclusion, local and regional development must be supported by planned finances, rather than by the financing of individual projects, specifically, financial instruments, the structure and flexibility of which is consistent with the objectives of the integrated program of development of local self-government.